Metode Triangulasi Dalam Penelitian Ilmu Komunikasi - Wiryanto, Wiryanto (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
AbstractTriangulation   is  the  application  and  combination  of  several research methodologies  in the study of the same phenomenon. It can be  employed  in  both  quantitative(validation) and  qualitative(inquiry) studies,  a method-appropriate strategy of founding  the credibility  of qualitative analyses,  becomes an alternative to " traditional criteria  like reliability and validity"  and the preferred line in the social sciences.By  combining   multiple   observers,  theories,   methods,   and empirical  materials,  researchers can hope to overcome the weakness or  intrinsic  biases  and the problems  that come  from single method, single-observer, single-theory  studies.  There  are  four  basic  type  of triangulation:  data  triangulation,  involving time,  space, and  persons; investigator  triangulation,  which  consist of the use of multiple,  rather than  single  observers;  theory  triangulation,  which  consists  of  using more   than   one   theoretical   scheme   in   the   interpretation   of   the phenomenon;  methodological triangulation, which involves using more than  one  method   and  may  consist  of  within-method   or  between- method strategies.